Analysis of the Management of Village-Owned Enterprises (BUMDESA) Karya Bakti to Improve Good Corporate Governance (GCG) in Pojok Village, Garum District, Blitar Regency - Septiawan, Bambang; Masrunik, Endah; Sholikah, Siti Maratus (Indonesian Journal of Entrepreneurship and Startups, 2023)
This study aims to find out how the Karya Bakti village-owned enterprise (BUMDesa) manages in improving village good corporate governance in Pojok Village, Garum District, Blitar Regency.The method used in this study is a qualitative method. Data collection techniques with observation, interviews and documentation. The data analysis technique used is data collection, data convention, data presentation, drawing conclusions/verification.The results of this study indicate that the management of Village-Owned Enterprises in Pojok Village, Garum District, Blitar Regency, has been running according to procedures and following government regulations and has implemented aspects of management strategy, as well as in managing Village-Owned Enterprises (BUMDesa) Karya Bakti Pojok Village inseparable from community cooperation